Development and validation of teachers' evaluation of school effectiveness scale (2009)
The study on school effectiveness is relatively new in Nigeria and there does not seem to be any instrumentthat can be termed "a school effectiveness scale which was evaluated by teachers. The name of the scale is teachers' evaluation of school effectivness scale (TESES). The scale was adminstered to secondary school teachers in thirty-six local government areas in Oyo, Ogun and Ekiti states. The samples for this study were selected using multistage random sampling method and 3000 teachers were selected. Four research questions were answered using factor analysis method. To purify the data, items with more than 0.40 on 2 or more factors were also removed. The overall instrument possesses high internal consistency and adequate construct validity. A satisfactory seven factors solutin was found which reflected teachers' evalaution towards school effectiveness. They are: school administration, school efficiency, students' empowerment and teachers' job performance. Teachers' job performance has the highest factor loading. The implications of the findings of the study are discussed.